Investigation of the compaction behavior of carbon fiber NCF for continuous preforming processes. Issue 11 (23rd November 2015) - Grieser, T.; Mitschang, P.
Abstract : This paper describes the experimental investigation of the compaction behavior of dry single‐ply and multi‐ply fabric stacks (preforms). Utilizing four biaxial (two 0°/90° and two ±45°) and one triaxial (0°±45°) carbon fiber NCF, differing in weight (300 g/m 2, 600 g/m 2 ) and type of stitching (tricot, pillar, hybrid), the influence of compaction speed, pre‐compaction cycles, number of layers, and stacking sequence on compaction force was examined. In contrast to other studies, the area of interest is limited to 40–50% fiber volume content (FVC), which is based on current continuous preforming conditions. The results showed that higher testing speeds result in increased compaction forces. Pre‐compaction cycles (up to 8) significantly reduce (up to 69%) the required compaction forces of preforms for continuous preforming. Furthermore, at an equal total superficial density (1800 g/m 2 ), 6‐ply preforms (300 g/m 2 each ply) require 75–88% higher compaction forces than 3‐ply preforms (600 g/m 2 each ply). This relation remains constant with decreasing or increasing total superficial density (ply number). Also the stacking sequence of 6‐ply preforms (300 g/m 2 each ply) remarkably influences the compaction force, whereby the stitching seam pattern and their alignment (superposition) to each other were the main influencing factors. POLYM. COMPOS., 38:2609–2625, 2017. © 2015 Society of Plastics Engineers